2015
DOI: 10.1038/nclimate2492
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of extreme La Niña events under greenhouse warming

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
403
3
6

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 575 publications
(452 citation statements)
references
References 29 publications
40
403
3
6
Order By: Relevance
“…Indeed, many of the observed trends in recent decades might be associated with these oscillations (Santos et al, 2012;Barton et al, 2013). Though predictions are controversial, some of these climate oscillations are expected to increase in amplitude or variance with climate change (Timmermann et al, 1999;Kuzmina et al, 2005;Sydeman et al, 2013;Cai et al, 2015), which would further mask monotonic trends.…”
Section: Water Temperatures and The Counteracting Roles Of Upwellingmentioning
confidence: 99%
“…Indeed, many of the observed trends in recent decades might be associated with these oscillations (Santos et al, 2012;Barton et al, 2013). Though predictions are controversial, some of these climate oscillations are expected to increase in amplitude or variance with climate change (Timmermann et al, 1999;Kuzmina et al, 2005;Sydeman et al, 2013;Cai et al, 2015), which would further mask monotonic trends.…”
Section: Water Temperatures and The Counteracting Roles Of Upwellingmentioning
confidence: 99%
“…It could be argued that we did not even apply an extra intensification due to RCP8.5, and this discrepancy would hold regardless of the future scenario. Considering that we are expected to experience even stronger ENSO events in the future than today (Cai et al, 2014(Cai et al, , 2015, we could have intensified this signal even more. However, our results with this realistic intensification already show the importance of capturing atmosphere-ocean teleconnections in climate simulations for reliable future simulations of the ecosystems.…”
Section: Scenario Selection and Future Simulationsmentioning
confidence: 99%
“…Recently, Yeh et al (2009) showed that under projected climate change the proportion of central Pacific ENSO events might increase. Furthermore, Cai et al (2014Cai et al ( , 2015 showed that current projections of climate change for the 21st century suggest an increased future likelihood of both El Niño and La Niña events. Based on the results of our study, potential increases in ENSO activity would results in an increased variability in the CO 2 and H 2 O exchange between the atmosphere and the tropical rainforests in these and similar regions.…”
Section: Resultsmentioning
confidence: 99%